Instructions for Administering the Canadian Occupational Performance Measure with Children Themselves. (2nd January 2023) - Verkerk, Gijs; van der Molen-Meulmeester, Lisanne; van Hartingsveldt, Margo; Alsem, Mattijs
Abstract: Aims: The Canadian Occupational Performance Measure (COPM) can be used to support children to clarify their needs themselves. However, for pediatric occupational therapists it is not sufficiently clear how to effectively use the COPM with children from 8 years of age. This study aimed to formulate specific instructions for using the COPM with children themselves, based on the experience of children, parents, and occupational therapists. In addition, professional consensus on the instructions was reached. Methods: A multi-stage approach was used to develop the instructions. Triangulation of methods was used to gather knowledge of how the COPM with children themselves is performed in daily practice: interviews with 23 children, questionnaires completed by 30 parents, interviews with 13 therapists, and 10 video recordings of COPM administration. Specific instructions were derived from this knowledge and consensus for these instructions was reached by Delphi method. Results: The data were analyzed and resulted in 40 specific instructions. Consensus of at least 80% amongst 10 occupational therapists, who regularly use the COPM with children, was achieved on each instruction. Conclusion: There is consensus on 40 specific instructions for administering the COPM with children. Following these instructions might help children to formulate their own goals for intervention.